Relationship of mood with characteristics of the disease among a group of psoriasis patients - Basińska, Małgorzata Anna; Szymańska, Liliana (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction. Psoriasis has a huge impact on the mental state of the patient, and especially the mood and experiences modify the course of the disease. Objective. The evaluation of the relationship between characteristics of the disease and subjective assessment of mood in patients with psoriasis. Material and methods. The study was conducted among 93 patients with psoriasis and 90 healthy persons as a control group. The following instruments were applied: a personal questionnaire, Psoriasis Area and Severity Index (PASI) and Profile of Mood State Questionnaire (POMS). Results. The study confirmed the relationship between characteristics of the disease and mood in patients with psoriasis. Women, younger persons, with shorter duration of the disease, more severe complaints and with higher PASI had a more negative mood than men, older persons, those who were sick longer, with less severe complaints and smaller PASI. Conclusions . An important part of treating patients with psoriasis should be improvement of their mental state, and especially the mood.